Valorisation et optimisation de l’utilisation d’un coagulant végétal pour la fabrication d’un fromage traditionnel - BENANI, Souad Touatia (My University, 2017)
Our work targets the determination of the dose of milk rennet and acidity that is ideal to obtain the most quick coagulation/clotting possible. We have concluded that a HAKKA solution Sylbium marianum of 10g would be the best answer to the question raised. We have thus succeeded to eliminate the acidification waiting time which represented a serious risk of contamination. Keywords
Keywords: الحليب; الحكة; المنفحة; الحموضة; Lait; présure; chardon marie; l’acidité; Milk; coagulation; acidification; Sylbium marianum.